The role of 18F-FDG PET/CT in patients with synchronous multiple primary malignant neoplasms occurring at the same time - Luo, Zhe Huang; Qi, Wan Ling; Jin, Ai Fang; Liao, Feng Xiang; Liu, Qian; Zeng, Qing Yun (Frontiers in Oncology, 2022)
Background: Synchronous multiple primary malignant neoplasms occurring at the same time(SMPMNS) isn’t currently uncommon in clinical oncological practice, however, the diagnostic performance of 18F-Fluorodeoxyglucose positron emission tomography/computed tomography(18F-FDG PET/CT) was unclear. Purpose: To evaluate the application of 18F-FDG PET/CT in patients with SMPMNS. Materials and Methods: Clinical and image data of 37 patients with SMPMNS, who have undergone 18F-FDG PET/CT From October 2010 to December 2020, were retrospectively analyzed. The kappa consistency test was performed to evaluate consistency of diagnostic performance between PET/CT and conventional imaging(CI). The sensitivity, specificity, and accuracy of PET/CT and CI in the detection of metastatic lesions were compared. Results: The retrospective diagnostic study include 74 lesions identified in 37 patients with SMPMNS, 94.6% patient had double primary tumors. 18.9% SMPMNS occurred in the same organ system, the respiratory tumors were the most common neoplasms types(43.2%), lung was the most common primary site(40.5%), overall survival rate of SMPMNS patients without metastases was longer than that of those with metastases(x2=12.627, p=0.000). The SUVmax, SUVmax ratio(larger SUVmax/smaller SUVmax) and DISUVmax [(larger SUVmax － smaller SUVmax)/larger SUVmax] of primary lesions ranged from 0.9 to 41.7(average of 12.3±7.9), 0.3 to 26.7(average 4.4±6.9) and 0.0% to 96.3%(average 50.3%±29.3%), respectively. The correct diagnosis of PET/CT and CI were poor in consistency (Kappa=0.096, P=0.173), The diagnostic results for revealing primary lesions(diagnosed and misdiagnosed) of PET/CT and CI were also in poor consistency(Kappa=0.277, p=0.000), the diagnostic performance of PET/CT was better than CI. In diagnosis of metastases, patient-based sensitivity, specificity and accuracy with PET/CT were 100.0%, 81.8%, 89.2% and with conventional imaging were 73.3%, 100.0%, 89.2%, both the sensitivity and specificity were significantly different, PET/CT has higher sensitivity(p=0.02), conventional imaging has higher specificity(p=0.02). Conclusions: 18F-FDG PET/CT improve the diagnostic performance of SMPMNS and is a good choice in imaging modalities for SMPMNS patients.